Cognitive Reserve in Older Adults: A Cluster Analysis - Carmen Moret-Tatay; Tatiana Quarti Irigaray; Irani Iracema de Lima Argimon; Camila Rosa de Oliveira (Psicologia: Teoria e Pesquisa, 2023)
Abstract Cognitive reserve (CR) is a construct generally associated with neurodegenerative diseases in aging. The aim of this paper was to examine the CR profiles of older adults at different stages of their lifespan and evaluate the importance of: (a) gender and CR; and (b) CR, cognition, and symptoms of depression. A sample of 195 older adults volunteered to participate in the study, and a cluster analysis was carried out on their responses in terms of the Cognitive Reserve Scale. The cluster analysis depicted two different profiles. Furthermore, women had a better CR than men. The results provide an important contribution to understanding the variables related to the CR construct.